Analisis Usaha Ekspor Kopi Indonesia Dan Malaysia Di Pasar Asean - Daspar; Nada Kamiliya; Meidiana Savitri; Nova Nur Eliza; Agnes Megawati (Jurnal Ekonomi dan Bisnis Digital, 2024)
Over the past three decades, the coffee culture has undergone a remarkable evolution. Initially a solitary indulgence, coffee consumption has transitioned into a communal experience, epitomized by gatherings with friends at trendy coffee establishments. The advent of the ASEAN Economic Community (AEC) in 2016 catalyzed a new phase for coffee exporters like Indonesia, necessitating an assessment of their competitive edge within the ASEAN 5 market. This assessment involves a thorough analysis, employing tools such as Revealed Comparative Advantage (RCA) and Export Product Dynamics (EPD), to gauge the dynamism and performance of Indonesian coffee products vis-à-vis their regional counterparts, Findings reveal a competitive landscape, with both Indonesian and Vietnamese coffee exports holding their ground in the ASEAN 5 market. Indonesia maintains an average RCA value of 10.16, while Vietnam boasts a higher total of 53.44, indicating a rising competitiveness in Vietnamese coffee exports compared to Indonesia's. Moreover, EPD analysis places both countries' coffee trades in the Rising Star quadrant, denoting a rapid and dynamic export performance, particularly driven by Indonesia's expanding share in ASEAN 5 markets, Given the burgeoning demand for coffee within this market, Indonesian authorities are keen on optimizing their export potential. This necessitates the formulation and implementation of strategic policies aimed at enhancing coffee production efficiency, thereby ensuring Indonesia's sustained success in penetrating and capitalizing on the ASEAN 5 coffee market.